Evaluasi Penyajian dan Pengungkapan Piutang Pihak Berelasi Berdasarkan PSAK 7 antara PT IM dengan PT KA - Riska Puji Astuti; Nurmala Nurmala; Eksa Ridwansyah (Politeknik Negeri Lampung, 2021)
PT IM is a subsidiary of PT KA engaged in Kwh Meter industry. PT KA purchases inventory of trade goods to PT IM which is used to meet the needs of the company's operational activities. The recording carried out by PT IM regarding the sale to the parties in this case is that PT KA must pay attention to the provisions stipulated in the Statement of Financial Accounting Standards (PSAK) No.7 regarding the parties concerned. The purpose of this writing is to evaluate whether the presentation and disclosure of receivables of parties related to PT IM has been in accordance with PSAK No.7. The data analysis method used is a qualitative analysis method. Based on the results and discussions, the author concluded that PT IM has not fully implemented the ministry stipulated in PSAK No.7 in terms of presentation and disclosure of receivable parties.